Widespread transcriptional alternations in oligodendrocytes in the adult mouse brain following chronic stress. Issue 2 (14th September 2017) - Liu, Jia; Dietz, Karen; Hodes, Georgia E.; Russo, Scott J.; Casaccia, Patrizia
ABSTRACT: Emerging evidence shows that oligodendrogenesis and myelination are highly responsive to behavioral experience, including physical activity and social experience. This form of myelin plasticity is being increasingly appreciated and examined in the prefrontal cortex (PFC), a critical brain region involved in complex emotional and cognitive behavior. However, it remains unclear whether myelination in other brain regions is affected by behavioral experience. Here we report that exposure to 4 weeks of chronic variable stress induced anxiety‐ and depressive‐like behavior in male adult mice. In concert with these behavioral responses, transcriptional analysis of PFC, and nucleus accumbens (NAc)—a brain region critical for reward response—revealed downregulation of transcripts encoding for myelin genes and oligodendrocyte‐specific genes. In contrast, upregulation of myelin‐related transcripts was observed in the corpus callosum (CC), whereas the amygdala (AMG) did not show significant changes. Shorter exposure to the same stressors induced behavioral changes to a less extent and was followed by a stress habituation period. However, reduced myelin and oligodendrocyte‐specific gene transcripts were detected as early as one week following stress exposure in the PFC and NAc. These data indicate that oligodendrocyte and their progenitors in multiple brain regions are responsive to stressful experiences and show distinctive and region‐specific patterns of gene expression. © 2017 Wiley Periodicals, Inc. Develop Neurobiol 78: 152–162, 2018